2021
DOI: 10.1177/00333549211026778
|View full text |Cite
|
Sign up to set email alerts
|

Increases in SARS-CoV-2 Test Positivity Rates Among Hispanic People in a Northern California Health System

Abstract: Racial/ethnic minority groups are disproportionately affected by the COVID-19 pandemic. We examined ethnic differences in SARS-CoV-2 testing patterns and positivity rates in a large health care system in Northern California. The study population included patients tested for SARS-CoV-2 from March 4, 2020, through January 12, 2021, at Stanford Health Care. We used adjusted hierarchical logistic regression models to identify factors associated with receiving a positive test result. During the study period, 282 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Additionally, African American people experience lower serum vitamin D levels [ 19 ]. Our findings are consistent with those of Rodriguez and colleagues who concluded that Hispanics experience increased odds of SARS-CoV-2 infection [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, African American people experience lower serum vitamin D levels [ 19 ]. Our findings are consistent with those of Rodriguez and colleagues who concluded that Hispanics experience increased odds of SARS-CoV-2 infection [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…A systematic review showed disproportionately higher COVID-19 related mortality in Hispanic populations 12 . In a large health system in Northern California, Hispanic populations were more likely than non-Hispanic populations to test positive for SARS-CoV-2 13 . A recent study of US-wide age- and sex-adjusted deaths further found that Hispanic populations experienced a rise in heart disease and cerebrovascular disease deaths in March-August 2020 as compared with March–August 2019 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Potential explanations for these findings include Hispanic overrepresentation in frontline or essential roles; a higher likelihood of living in denser communities and multigenerational households, making it more challenging to isolate and contain exposure risk; differential burden of underlying comorbidities such as diabetes; and language differences that may limit access to public health messaging 13 . The links between COVID-19 and downstream effects on the traditional leading causes of death in the US may lead to long-term disparities beyond the pandemic if their structural underpinnings remain unaddressed.…”
Section: Discussionmentioning
confidence: 99%